An assessment of informational needs of breast cancer among patients and adults in general publicand the effectiveness of a tailor-made information package for patients in Sri Lanka - Kuruppu, D.C.; Wijeyaratne, C.N.; Gunawardane, N.; Amarasinghe, I. (National Symposium on Best Practices for Innovations on cancer prevention, control and palliative care 2018, 2018)
Breast cancer (BC) is the commonest cancer in Sri Lanka. The provision of relevant and accurate information in a social-culturally appropriate manner will lead to proper understanding of the disease, treatment options, and BC management.
Keywords: An assessment of informational needs of breast cancer among patients and adults in general publicand the effectiveness of a tailor-made information package for patients in Sri Lanka